Safety evaluation of synthesised DNA oligonucleotides as a food additive - EFSA Panel on Food Additives and Flavourings (FAF); Maged Younes; Gabriele Aquilina; Gisela Degen; Karl‐Heinz Engel; Paul Fowler; Maria Jose Frutos Fernandez; Peter Fürst; Ursula Gundert‐Remy; Rainer Gürtler; Trine Husøy; Melania Manco; et al. (EFSA Journal, 2023)
Abstract The EFSA Panel on Food Additives and Flavourings (FAF) was requested to evaluate the safety of synthesised DNA oligonucleotides as a new food additive, in accordance with Regulation (EC) No 1331/2008. Considering that the additional information requested by the Panel during the risk assessment was not provided by the applicant, the assessment was concluded on the basis of the sole information available in the application. The proposed food additive consists of purified synthetic DNA sequences intended to be used for traceability purposes, alone or combined with carriers. Information provided by the applicant on the identity, characterisation and production process of the proposed food additive was considered insufficient. The Panel considered that the product specifications as proposed by the applicant do not adequately define and characterise the proposed food additive. The applicant proposed for the food additive the maximum use levels of 0.001 mg/kg for a variety of food categories. The food additive was also proposed as a Group I additive at a specific maximum level of quantum satis. The applicant did not provide exposure estimates according to the EFSA ANS Panel guidance (2012). No biological or toxicological data were provided by the applicant for the proposed food additive. Considering the inadequate information available and the uncertainty introduced by the proposal at quantum satis, along with the insufficient specifications, the Panel could not conclude on the safety of the food additive as proposed and described by the applicant.